The meaning of culture dissemination in Japanese intergenerational learning - Suzuki, Naoko (Formazione & insegnamento, 2014)
Japan is one of many countries in the world facing the increasingly serious issues of an ageing population combined with a very low birth rate. The impact upon Japanese society of this situation is enormous in both the medium and long term, and a number of measures have been introduced, both by local and central governments, to try and cope. At the same time, over the past decade serious crimes against and by children have also caused grave concerns. In this context, intergenerational learning has been strongly encouraged in the hope that it may not only resolve communication breakdown among the different generations but may also create a wide range of spin-off effects. One of the conspicuous features in Japan is that intergenerational learning has the strong potential to work as a means of culture dissemination from the elderly to small children. This study intends to clarify general trends in Japanese intergenerational learning by explaining why the latter is being focused upon in the present day, and above all, to demonstrate through analysis of papers and case studies how the dissemination of culture is of importance to this country. It is indicated that culture dissemination could serve as the driving force to promote intergenerational learning, to maintain and/or revitalize social solidarity and strengthen the community bond.